Anti-inflammatory effects of dexamethasone and meloxicam on Borrelia burgdorferi-induced inflammation in neuronal cultures of dorsal root ganglia and myelinating cells of the peripheral nervous system. Issue 1 (December 2015) - Ramesh, Geeta; Meisner, Olivia; Philipp, Mario
Abstract Background Lyme neuroborreliosis (LNB), caused by the spirocheteBorrelia burgdorferi (Bb), could result in cognitive impairment, motor dysfunction, and radiculoneuritis. We hypothesized that inflammation is a key factor in LNB pathogenesis and recently evaluated the effects of dexamethasone, a steroidal anti-inflammatory drug, and meloxicam a non-steroidal anti-inflammatory drug (NSAID), in a rhesus monkey model of acute LNB. Dexamethasone treatment significantly reduced the levels of immune mediators, and prevented inflammatory and/or neurodegenerative lesions in the central and peripheral nervous systems, and apoptosis in the dorsal root ganglia (DRG). However, infected animals treated with meloxicam showed levels of inflammatory mediators, inflammatory lesions, and DRG cell apoptosis that were similar to that of the infected animals that were left untreated. Methods To address the differential anti-inflammatory effects of dexamethasone and meloxicam on neuronal and myelinating cells of the peripheral nervous system (PNS), we evaluated the potential of these drugs to alter the levels of Bb-induced inflammatory mediators in rhesus DRG cell cultures and primary human Schwann cells (HSC), using multiplex enzyme-linked immunosorbent assays (ELISA). We also ascertained the ability of these drugs to modulate cell death as induced by live Bb in HSC using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) viability assay and the potential of dexamethasone to modulate Bb-induced apoptosis in HSC by the TUNEL assay. Results Earlier, we reported that dexamethasone significantly reduced Bb-induced immune mediators and apoptosis in rhesus DRG cell cultures. Here, we report that dexamethasone but not meloxicam significantly reduces the levels of several cytokines and chemokines as induced by live Bb, in HSC and DRG cell cultures. Further, meloxicam does not significantly alter Bb-induced cell death in HSC, while dexamethasone protects HSC against Bb-induced cell death. Conclusions These data help further explain our in vivo findings of significantly reduced levels of inflammatory mediators, DRG-apoptosis, and lack of inflammatory neurodegenerative lesions in the nerve roots and DRG of Bb-infected animals that were treated with dexamethasone, but not meloxicam. Evaluating the role of the signaling mechanisms that contribute to the anti-inflammatory potential of dexamethasone in the context of LNB could serve to identify therapeutic targets for limiting radiculitis and axonal degeneration in peripheral LNB.